Pemasangan Sistem Otomatis pada Lampu Berbasis Sensor Cahaya (Photocell) di Wilayah RT 17 Kelurahan Sepinggan - Muhamad Hasyim Tuankotta; Dwy Anugerah Saputra; Febriani Febriani; Rana Fitriani; Mutia Amrilla; Dinda Dinda; Randy Khairullah Iqbal; Rayhan Sultan Hafidz; Samuel Candra Brain Aruan; Indra Tri Sakti; Wagimin Wagimin; Wahyu Ismail Kurnia (Abdimas Universal, 2024)
As public facilities develop, technological advances in the electrical system are also inevitable. These developments need to be followed up to increase work efficiency in society and optimize devices in public spaces. Especially in the RT 17 area, Sepinggan Village, the lighting facilities at the Tahfidz Adz Dzikru school are still working or operated manually. The automatic lighting is made to avoid excessive energy waste when local authorities forget to operate the lights on time. Failure to turn off the lights is a form of energy waste. Therefore, it is necessary to create a system that can operate the lights automatically. Installing lights with automatic Photocell switches is a solution to make it easier for the Tahfidz Adz Dzikru school to operate lights that can turn on or off without having to operate them manually and of course can reduce excessive energy waste. Based on the results of consolidation with partners, this service activity is focused on modifying the terrace lights at Adz Dzikru Elementary School by adding photocell technology so that the operation of the lights can take place automatically. Apart from that, knowledge and skills in photocell installation were also transferred to several residents in order to anticipate future obstacles and developments. The results of the activities carried out were the installation of photocell technology at 2 light points on the terrace of the Tahfidz Adz Dzikru School and an increase in partners' knowledge and skills related to photocell technology.